Development of Project-Based Digital Teaching Modules in Social Studies Learning on the Critical Thinking Skills of Elementary School Students - Yuyun Dwi Haryanti; Devi Afriyuni Yonanda; Ani Rosidah; Mahpudin; Minnatul Maula (Universitas Negeri Malang, 2025)
Abstract: Critical thinking skills are used by students to face global challenges. This study aims to develop project-based digital teaching modules through social studies learning on students' critical thinking skills in elementary schools. This study is a developmental study using the Borg and Gall model. The subjects of the study are teachers and students of phase C of class V in social studies learning in Majalengka district. Data was collected through interviews, questionnaires, and critical thinking tests, and SPSS was used to analyze them. Data was collected through interviews, questionnaires, and critical thinking tests, with SPSS used for analysis. The results of the study show that teachers need project-based digital teaching modules in social studies learning. The products produced are valid for 86% material experts, 87% media experts, 87% linguists. The Ngain value in the experimental class was 0.73 while the average Ngain value in the control class was 0.24, which means that project-based digital teaching modules are more effectively used in social studies learning. The practicality of project-based digital teaching modules from the overall results of teacher and student questionnaires showed that a score of 91% of the category was very good for use in social studies learning. The project-based digital teaching module developed helps teachers in the social studies teaching process so that it significantly impacts the improvement of students' critical thinking skills.Abstrak: Keterampilan berpikir kritis digunakan oleh siswa untuk menghadapi tantangan global. Penelitian ini bertujuan untuk mengembangkan modul pembelajaran digital berbasis proyek melalui pembelajaran ilmu sosial guna meningkatkan keterampilan berpikir kritis siswa di sekolah dasar. Penelitian ini merupakan penelitian pengembangan yang menggunakan model Borg dan Gall. Subjek penelitian adalah guru dan siswa kelas V fase C dalam pembelajaran ilmu sosial di Kabupaten Majalengka. Data dikumpulkan melalui wawancara, kuesioner, dan tes berpikir kritis, dan dianalisis menggunakan SPSS. Data dikumpulkan melalui wawancara, kuesioner, dan tes berpikir kritis, dengan SPSS digunakan untuk analisis. Hasil penelitian menunjukkan bahwa guru membutuhkan modul pembelajaran digital berbasis proyek dalam pembelajaran sejarah. Produk yang dihasilkan valid untuk 86% ahli materi, 87% ahli media, dan 87% ahli bahasa. Nilai Ngain di kelas eksperimen adalah 0,73 sementara nilai Ngain rata-rata di kelas kontrol adalah 0,24, yang berarti modul pembelajaran digital berbasis proyek lebih efektif digunakan dalam pembelajaran sejarah. Kegunaan modul pembelajaran digital berbasis proyek dari hasil keseluruhan kuesioner guru dan siswa menunjukkan skor 91% dalam kategori sangat baik untuk digunakan dalam pembelajaran ilmu sosial. Modul pembelajaran digital berbasis proyek yang dikembangkan membantu guru dalam proses pengajaran ilmu sosial sehingga secara signifikan mempengaruhi peningkatan keterampilan berpikir kritis siswa.